TRANSFORMATION OF BEHAVIORAL FINANCE AS A RESULT OF CHANGES IN ECONOMIC BEHAVIOR MODELS - Barabash, Lesia (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2020)
The development of economy and its fluctuations sometimes acquire disastrous forms for countries and even the world community; and individual unexpected financial ups and downs of powerful corporations always attract attention of practitioners as well as researchers. They both look for the reasons for these phenomena, primarily referring to classical finance. However, their explanations do not always look convincing; they ignore the elusive essence of their incentive factor. And it was perseverance and a combination of the opposite that contributed to the emergence of behavioral finance, which focused the search on the social and psychological aspects of phenomena. Each period of economic development was marked by a number of authentic prerogatives and goals that shaped the behavior of the individual. Generalization of individuals similar in priorities and directions of implementation of actions formed the basis of models of economic behavior. The change in these models was due not only to scientific and technical progress, but also to the role of person in society, their identification as a separate participant or a participant of the collective society, as a component of the whole. The transition from Homo economicus, whose purpose of operation was rational egoistic enrichment, to Homo creativus, who acquires the understanding of their own identity and the need to improve and realize abilities, leads to the emergence of an opinion about the irrationality of the nature of the individual’s economic behavior. Further changes in the socio-economic environment led to the formation of a behavioral model for social climbers, for whom monetary resources are not the goal for their work, but rather a means of realizing egoistic ascension. The command system formed the behavior model of Homo soveticus, which erased the boundaries of the personal for the sake of collective goals, causing the emergence of a «collective mentality». And the assertion of a democratic society of our time contributed to the emergence of RREEMM (resourceful, restricted, evaluating, expecting, maximizing man) and Click models, in which an individual shows his qualities and achieves goals in conditions of limited resources and information, but with excessive confidence in his own strengths and knowledge. and decisions in most cases are made by impulsive pressing of a button.